The World Bank Group's Response to the Global Economic Crisis : Phase 2 - Independent Evaluation Group (Washington, DC: World Bank Group, 2015)
This second report of a two-phase evaluation of the World Bank Groupapos;s unprecedented response to the 2008-09 global economic crisis addresses questions raised by the findings of the first phase evaluation regarding the Bankapos;s crisis lending in the financial, fiscal, and social protection areas, and the adequacy of its lending instruments. Regarding International finance corporation (IFC), this second phase evaluation finds that the corporation did not achieve an increased volume of investments as a reflection of a strategic choice to protect its portfolio as well as an overestimation of the prospective deterioration in portfolio quality. This evaluation assesses the World Bank Groupapos;s response to the global economic crisis. This is the second phase of a two-phase Independent Evaluation Group (IEG) evaluation of the World Bank Group response to the unprecedented global economic crisis of 2008-09. This second phase report evaluates relevance and efficiency of new crisis lending through financial, fiscal management, and social protection operations in response to questions rose in the first phase evaluation.